Analisis Faktor Penyebab Anemia pada Ibu Hamil di Puskesmas Kairatu Seram Barat - Amanupunnyo, Notesya Astri; Shaluhiyah, Zahroh; Margawati, Ani (Universitas Aisyah Pringsewu, 2018)
Kairatu Health Center is 1 of 17 health centers in the district of West Seram with the prevalence of anemia is high at 45.63 percent and 2017 anemic order to 7 of 10 diseases in PHC Kairatu. Prevalence is quite high compared to world 38,2 and in Indonesia 37.1 percent. The purpose of this study was to determine anemia in pregnant women using cross sectional and the total sample of 120 people.Data collected interviews and questionnaires, then analyzed by univariate, bivariate and multivariate. Anemic respondents were more than those who were not anemic with the highest category of moderate anemia. Most of the respondents' ages are not at risk, slight parity, distant pregnancy distance, most trimester 3 gestational, but prenatal care is not up to standard. The test results for the cost of consuming iron supplements (p=0.030) and coffee/tea consumption (p=0.004) correlated with the incidence of anemia in pregnant women. The influential variables were consumption of iron supplements (OR=17,763) and coffee/tea consumption (OR=17,590) while age a protective factor (p=0,196). Pregnant women who do not adhere to consuming Fe tablets and often consume coffee/tea greatly affect the prevalence of anemia. Anemic education and prevention through various media and controlling the distribution of Fe tablets and consumption of Fe tablets through drug consumption cards can be carried out continuously to suppress pravalence anemia.